Oxygen injection during fast vs slow passivation in aqueous solution. (July 2021) - Yu, Xiao-Xiang; Han, Junsoo; Scully, John R.; Marks, Laurence D.
Abstract: The typical defect reactions at the metal/oxide interface, which explain the growth and breakdown of passive oxide films in corrosion, include creating metal and oxygen vacancies. While the creation and coalescence of metal vacancies are well documented, there are relatively few observations on the nanoscale details of oxygen transport near the metal/oxide interface. We report here a new mechanism of oxygen injection into the metal. Fast and slow passivation (i.e., corrosion involving both oxide film growth and direct dissolution) of NiCr and NiCrMo alloys was performed by galvanostat experiments in 0.1 M NaCl (pH 4) deaerated solution. Localized regions of an unexpected nonequilibrium metal-based oxygen solid solution were observed beneath the outer (externally formed) oxides, and the saturated oxygen atoms distorted the fcc metallic lattices. Oxygen injection into the metal is more significant at a fast growth rate due to a large passivation current density for the NiCr alloy. In this case, there is a high volume of rock salt Ni(Cr)O nanocrystals in the O-rich Ni(Cr) substrate, which is consistent with greater susceptibility to chloride-induced breakdown found in potentiostat experiments. The addition of Mo promotes the formation of the corundum phase in the outer oxide layer for NiCrMo, which changes the transport mechanism as well as the diffusivity of oxygen through the oxide film and across the metal/oxide interface. Graphical abstract: Image, graphical abstract